Dimensi Kearifan Lokal Dalam Serat Bima Suci (Akulturasi Harmonis Ajaran Islam dengan Budaya Jawa) - Purwadi - (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2005)
One of the literatures that fill ethics and mysticism is Serat Bima Suci. It was created by Yasadipura I in the earlier period of Surakarta. Historically Serat Bima Suci, is still related with Serat Nawaruci that was created by Empu Siwamurti in the end period of Majapahit Kingdom. Serat Bima Suci is a literature that has acculturation between Javaism, Hinduism and Islamism. The harmony of relation between God, human, and nature become focal of Serat Bima Suci.